2015
DOI: 10.1155/2015/563893
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Ultrasound Surveillance for Hepatocellular Carcinoma in a Canadian Centre and Determinants of Its Success

Abstract: A high rate of HCC surveillance success was achieved using US alone when performed regularly in a specialized hepatobiliary centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…It is becoming increasingly evident that ultrasound limitations contribute to deficiencies in HCC surveillance effectiveness in clinical practice. A prior study from Italy demonstrated ultrasound failed to detect 30% of HCC at an early stage, while another study from Canada reported ultrasound failure in approximately 25% of cases . The authors postulated this was due to a combination of aggressive tumour biology and surveillance ultrasound's imperfect sensitivity; however, they could not determine the relative contribution of each factor.…”
Section: Discussionmentioning
confidence: 96%
“…It is becoming increasingly evident that ultrasound limitations contribute to deficiencies in HCC surveillance effectiveness in clinical practice. A prior study from Italy demonstrated ultrasound failed to detect 30% of HCC at an early stage, while another study from Canada reported ultrasound failure in approximately 25% of cases . The authors postulated this was due to a combination of aggressive tumour biology and surveillance ultrasound's imperfect sensitivity; however, they could not determine the relative contribution of each factor.…”
Section: Discussionmentioning
confidence: 96%
“…As the prognosis of HCC depends largely on the stage at which the tumor is detected, detection of HCC early in its development is critical to improve the survival of affected patients [218–220]. Although ultrasonography (US) is the most widely used modality for HCC screening and surveillance, the reported sensitivity of surveillance US is in the range of 40–81% with specificity of 80–100% [221225].…”
Section: Diagnosis and Surveillancementioning
confidence: 99%
“…This suggests that, despite notable technical advancements (US machines, probes, modules, and applications), detection rate did not improve. Yet, this statement is contradicted by Khalili K et al, which, based on a more recent experience reported that detection rate did significantly increase in the latter part of the 2000s decade [59]. However, these relatively optimistic findings might be counterbalanced by a recently published Korean report, which revealed substantial discrepancies in screening quality between healthcare providers.…”
Section: Factors Affecting Us Performancementioning
confidence: 92%